The sun is rising in the East: Dual-class shares and the competitive landscape of technological industries in Asia - LIANG, Hao (Institutional Knowledge at Singapore Management University, 2022)
There has recently been a relaxation of listing regulations to accommodate and attract firms going public with dual-class shares (DCS), notably in Asia. We examine the value implications of DCS adoption by employing an event study around a regulatory change allowing DCS listings in Hong Kong. We find negative market reactions around these regulatory discussions for firms already listed in Hong Kong, especially for firms in technology (tech) sectors. However, the market reaction turned positive for tech firms during Hong Kong’s first DCS listing. We identify two distinct channels that influenced shareholders’ perspectives on DCS: the competition channel, which dominated in the earlier discussions, as firms facing more competitive threats experienced lower returns; and the capital channel, which arose later, as it became clear that the regulatory change would enable all tech firms to attract more institutional capital.